FACTORS AFFECTING THE ACCURACY OF FINANCIAL REPORTING WITH GOING CONCERN AUDIT OPINION AS A MODERATION VARIABLE - Yumaiza, Tesa; Yunilma, Yunilma; Rahmawati, Novia (Jurnal Kajian Akuntansi dan Auditing, 2026)
A going concern audit opinion is critical for stakeholders to evaluate an entity’s financial health and predict its ability to continue operations in the foreseeable future. This study aims to examine the factors that affect the accuracy of financial reporting with the audit opinion going concern as a moderation variable. The research methodology uses secondary data analysis from the annual reports of property and real estate sector companies listed on the Indonesia Stock Exchange for the period 2020-2024, with a total of 60 samples obtained through purposive sampling methods from www.idx.co.id sites. Data analysis was carried out by logistic regression using SPSS 27. The results of the study show that profitability and liquidity have no effect on the accuracy of financial reporting, while solvency and company size have a positive effect on the accuracy of financial reporting. In addition, the going concern audit opinion is not able to moderate the influence between profitability and company size on the accuracy of financial reporting, but it is able to moderate the influence between liquidity and solvency on the accuracy of financial reporting.